Selective foraging by non-native rainbow trout on invertebrates in Patagonian streams in Argentina - Di Prinzio, Cecilia Yanina (2015)
Background It is well known that fish predation alters ecosystem processes by top-down effects. Salmonids are described as aggressive, visually and size-selective predators. Thus, prey selection by the non-native rainbow trout was examined on a seasonal basis at two streams: Nant y Fall (NyF) and Cabeza de Vaca (CVA) at Patagonia, a region where this kind of information is lacking. Results The benthos density at NyF was higher than that at CVA, and at both streams, riffles supported higher macroinvertebrate densities than pools. The diet of trouts from both streams was dominated by aquatic macroinvertebrates, was diverse, and was varied seasonally. The individuals represented in the stomach contents were among the largest available at the streams. Diet diversity peaked during spring at NyF and during summer at CVA, whereas at both streams, the niche width peaked during spring. Prey selectivity varied seasonally. The selected preys included both aquatic (Gasteropoda, Crustacea, Plecoptera, Trichoptera, Ephemeroptera, Coleoptera, Diptera, and Odonata) and terrestrial organisms (adult dipterans, Oligochaeta, Araneae, Homoptera, Hymenoptera, Orthoptera, and Hemiptera). Some infaunal invertebrates like oligochaetes and some small Coleoptera and Diptera larvae (mainly Chironomidae) were not selected by trouts. Conclusions Despite of the overall dominance of trichopteran species, the composition of the diet of the rainbow trout varied seasonally. This fish positively selected both aquatic and terrestrial organisms. We observed that in both streams, trouts consumed the larger individuals available in those environments.